Yamasaki 'redux' : Otoño - Fernandez-Galiano, Luis (2002)
Reseña biográfica del Arq.Minoru Yamasaki, autor de las <Torres Gemelas>
Keywords: ESTADOS UNIDOS; NUEVA YORK; TORRES; HISTORIA; SIGLO XX; CRITICA; DIARIOS; BIOGRAFIAS; YAMASAKI, MINORU